Impact of sialendoscopy on improving health related quality of life in patients suffering from radioiodineinduced xerostomia - Bulut, Olcay Cem; Haufe, Sabine; Hohenberger, Ralph; Hein, Matti; Kratochwil, Clemens; Rathke, Hendrik; Plinkert, Peter K.; Baumann, Ingo; Holland-Letz, Tim; Haberkorn, Uwe; Flechsig, Paul (Nuklearmedizin - NuclearMedicine, 2018)
Introduction: Xerostomia following radioiodine therapy (RIT) in patients suffering from differentiated thyroid cancer is a common side effect in 2 % to 67 % of patients treated with radioiodine (I-131). In order to evaluate the impact of sialendoscopy on health related quality of life (HRQOL) in patients suffering from therapy induced sialadenitis and xerostomia, we analyzed findings from two dedicated questionnaires (Xerostomy Questionnaire XQ and Xerostomy Inventory XI) in patients before and three months after sialendoscopy. Procedures: In total, 12 patients suffering from differentiated thyroid carcinoma (10 women and 2 men) were evaluated. All patients had experienced conservative management. Patients were offered a sialendoscopy procedure if no major contradictions were present. Patients who denied the procedure formed the control group. Pre- and (three months) postoperative HRQOL was measured with the Patient Reported Outcome Measures (PROM) Xerostomia Questionnaire (XQ) and the Xerostomia Inventory (XI), as well as by a pre- and post-interventional salivary gland scintigram. Patients were graded according to their sialendoscopical findings. Results: Interventional group presented with significant improvements in HRQOL measurements regarding XQ and XI-scores three months postoperatively. Control group showed no significant changes in the XQ or the XI scores. Number of RIT and cumulative activity of I-131 did not correlate with higher disease grade in regards to sialendoscopical findings nor did it correlate with higher XQand XI scores. Pre- and post-interventional salivary gland scintigram stated that parotid glands are more severely damaged than submandibular glands (SMG), but no significant scintigraphically changes could be detected after sialendoscopy. Conclusion: Sialendoscopy in patients suffering from therapy induced sialadenitis and xerostomia seems to be beneficial when evaluating the impact on HRQOL. Functional parameters measured by salivary gland scintigram did not show significant changes in post-interventional scintigrams.
Keywords: Sialendoscopy; radioiodine therapy; classification sialendoscopy; health-related quality of life; xerostomia; grading and classification sialadenitis